2020
DOI: 10.1177/2372732220943639
|View full text |Cite
|
Sign up to set email alerts
|

The Social Psychology of Racially Biased Policing: Evidence-Based Policy Responses

Abstract: Police killings of unarmed African Americans, such as George Floyd in 2020, continue to cause nationwide protests and calls for change. Psychological science knows much about biased policing and can inform policy to promote equitable policing. Social psychology’s extensive findings on stereotyping, attitudes, and intergroup relations help clarify the role of officer racial bias. This article reviews implicit and explicit bias, race-crime stereotypes, intragroup bias, ingroup favoritism, stereotype threat, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Similarly, in contrast to the broad behavioral and social science literature on racial biases and disparities, and even the disproportionate involvement of individuals of color in the justice system, there are relatively few studies on the disproportionate inappropriate use of force toward people of color and other minoritized groups. Recent reviews of this literature revealed mixed findings: Though disproportionate impacts on minoritized groupsare clear, causal factors are less so-in part due to a variety of methodologies employed and challenging confounds accruing from, for example, the interactions of officer race/ethnicity and civilian race/ ethnicity (Correll et al, 2014;Goff & Kahn, 2012;Kahn & Martin, 2020) understanding aggression as the product of basic drives, to learned behavior, to cognitive evaluations and representations (Eron, 1994).…”
Section: Theory and Research Related To The Inappropriate Use Of Force By Police And Its Disproportionate Impact On Minoritized Populatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in contrast to the broad behavioral and social science literature on racial biases and disparities, and even the disproportionate involvement of individuals of color in the justice system, there are relatively few studies on the disproportionate inappropriate use of force toward people of color and other minoritized groups. Recent reviews of this literature revealed mixed findings: Though disproportionate impacts on minoritized groupsare clear, causal factors are less so-in part due to a variety of methodologies employed and challenging confounds accruing from, for example, the interactions of officer race/ethnicity and civilian race/ ethnicity (Correll et al, 2014;Goff & Kahn, 2012;Kahn & Martin, 2020) understanding aggression as the product of basic drives, to learned behavior, to cognitive evaluations and representations (Eron, 1994).…”
Section: Theory and Research Related To The Inappropriate Use Of Force By Police And Its Disproportionate Impact On Minoritized Populatiomentioning
confidence: 99%
“…Importantly, social identity theory (Tajfel et al, 1979) provides a basis for understanding how racial and ethnic distinctions become salient and spark conflict. Furthermore, a raft of social-psychological theories related to biased perceptions and stereotyping can account for officers' inappropriate use of force against people of color or other minoritized groups (Dukes & Kahn, 2017;Kahn & Martin, 2020).…”
Section: Theory and Research On Predictors Of The Disproportionate Use Of Force Against Minoritized Groupsmentioning
confidence: 99%
“…“Cognitive bias” has been identified as a driving factor concerning the use of inappropriate force by the police, especially towards people of color and other minoritized groups (Boxer et al, 2021; Dukes and Kahn, 2017; Kahn and Martin, 2020; Peeples, 2020). Combating cognitive biases that negatively affect police–citizen encounters poses serious challenges for the police (Peeples, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on policing, at the individual level, officers' explicit attitudes, which are consciously endorsed and acknowledged beliefs, can influence behaviour with racial minorities through intentional actions. Implicit attitudes, which occur underneath one's awareness, can similarly influence behaviours in subtle ways, despite a lack of intentionality (Kahn & Martin, 2020). The characteristics of use of force situations themselvesnecessitating fast decisions with large amounts of stimuli in stressful environmentsmake it more likely that implicit stereotypes are relied upon (Fazio & Olson, 2003).…”
mentioning
confidence: 99%
“…At the departmental level, policing policy, practice, and culture also affect use of force behaviours and disparate outcomes. How and where officers are deployed, and the types of training, use of force policies, and cultural norms within a department influence an officer's likelihood of using force and against whom (Kahn & Martin, 2020). Refining our knowledge of the source of racial bias in police force helps to identify risk factors, and how and where to intervene.…”
mentioning
confidence: 99%